Propuesta de tratamiento de vertimientos provenientes de termales del municipio de Paipa, a través de potenciales medios adsorbentes generados con base en recursos naturales y residuos agropecuarios disponibles en la provincia de Tundama en el departamento de Boyacá. (2022)
The objective of this degree work was to develop a proposal for the treatment of discharges from thermal springs in the municipality of Paipa, through potential adsorbent media, based on natural resources and agricultural waste available in the province of Tundama in the department from Boyaca. It began with a contextualization of the origin and characteristics of hot springs in Colombia and in the world, comparing four different geographical areas, in order to select a guide for the sampling campaign carried out, selecting the research in the VCM, since it provided More information to take into account to carry out a campaign that takes into account the most representative parameters.